Interest of hair tests to discriminate a tail end of a doping regimen from a possible contamination in case of challenging an anti‐doping rule violation. V. Case reports involving trimetazidine, a drug where the concentration after a single 20 mg dose has been established - Kintz, Pascal; Ameline, Alice; Gheddar, Laurie (Drug testing and analysis, 2025)
The identification of trimetazidine, a medicine used for treating stable angina pectoris and for preventing angina attacks, has been recently observed in doping cases involving high profile athletes from various countries over the world. In all the files where the authors have been involved, the urine concentration of trimetazidine was low (<2 ng/mL), and the athletes argued that contamination was the source of their adverse analytical finding. It is possible to challenge imposed sanctions in relation to an adverse analytical finding, but it is the responsibility of the athlete to demonstrate he/she is innocent and can qualify for no fault or negligence. When the delay between the urine collection and the notification of the violation was not too long (less than 6 months), these athletes requested a head hair test. Trimetazidine was analyzed by an original LC–MS/MS method involving pH 9.5 borate buffer overnight incubation of 20 mg and subsequent solvents extraction in presence of trimetazidine‐D8 used as internal standard. Linearity was verified from 1 to 200 pg/mg (R2 = 0.9987). Limit of detection of the method was 0.1 pg/mg. The hair specimen of a male subject, collected 4 weeks after single oral ingestion of 20 mg trimetazidine, tested positive at 146 pg/mg in the corresponding segment. Concentrations of trimetazidine measured in several hair specimens (n = 5) collected from athletes challenging their anti‐doping rule violation were below 1 pg/mg, which is consistent with incidental exposure due to contamination. This is the first evidence that trimetazidine is incorporated in human hair after a single therapeutic dose administration. From ingestion to hair incorporation